A retroperitoneal bronchogenic cyst: a rare cause of a mass in the adrenal region. Issue 10 (1st October 2001) - Haddadin, W J; Reid, R; Jindal, R M
Abstract : This report documents a bronchogenic cyst presenting as an adrenal tumour in a 51 year old man with persistent epigastric pain. The cyst is regarded as a developmental abnormality of the primitive foregut, which typically occurs in the chest. Subdiaphragmatic, and retroperitoneal locations in particular, are unusual. The differential diagnosis of a bronchogenic cyst in the retroperitoneum includes cystic teratoma, bronchopulmonary sequestration, cysts of urothelial and mullerian origin, and other foregut cysts.